Evaluating Interoperability in EV Wireless Charging Systems: A Framework-Based Comparative Approach - Narputro, Panji; Suryana, Anang (Journal of Electronic Voltage and Application, 2025)
Wireless Power Transfer (WPT) technology has emerged as a promising solution for convenient and safe Electric Vehicle (EV) charging. However, the lack of interoperability between wireless charging systems developed by different manufacturers due to the diversity of international standards such as SAE J2954, IEC 61980, and ISO 15118 poses significant barriers to large-scale adoption. This paper presents a comprehensive review of the current WPT standard and its technical specifications, and is followed by an analysis of interoperability challenges in EV charging systems. Based on these identified gaps, we propose a conceptual framework to evaluate technical interoperability across various WPT implementations. This framework certainly also considers key parameters such as frequency alignment, coil compatibility, power level, communication protocol, and safety features. The results of this study provide insights for developers, manufacturers, and regulators in aligning the WPT system to support EV charging infrastructure that can be operated in the future.